P-219 Impact of Premedication with Steroids on Formation of Antibodies to Infliximab in Pediatric Inflammatory Bowel Disease: A Cross-Sectional Study. (March 2016) - Gjikopulli, Arieda; Molle-Rios, Zarela; He, Zhaoping
Abstract : Background: Infliximab is a chimeric monoclonal antibody against tumor necrosis factor α approved for the induction and maintenance of remission in Crohn's disease (CD) and ulcerative colitis (UC). Loss of response to the medication is a clinical challenge and has been associated with drug immunogenicity and formation of antibodies to infliximab (ATI). Reported ATI prevalence in literature has been anywhere from 8% to 60%. The role of premedication with corticosteroids in preventing ATI formation and potentially infusion reactions is controversial and poorly studied in children. Premedication with intravenous (IV) methylprednisolone prior to each infliximab infusion is routinely practiced in our institution as a method to decrease ATI formation. This cross sectional study is aimed to investigate the prevalence of ATI in the setting of premedication with steroids and identify additional variables that may affect ATI formation and infliximab levels. Methods: Pediatric patients (n = 130) with inflammatory bowel disease and treated with ifliximab were identified and their first ATI testing was collected. Additional data recorded included ifliximab level, BMI percentile, CRP, fecal calprotectin, albumin and concomitant use of the immunomodulator therapy at the time of testing. Data were compared between the ATI positive and negative groups and between detectable and undetectable ifliximab level groups and analyzed with descriptive statistics. Continuous variables were assessed by t -test and categorical variables by chi-square contingency analysis. P value <0.05 indicates statistical significance. The study was approved by the institutional review board. Results: Total 130 patients; 55 females and 75 males with mean age 15 ± 3.4 years were included in the study. ATI testing was obtained for monitoring (56%), concern for loss of response (42%) or infusion reaction (2%). The overall prevalence of positive ATI was 45% (59/130). ATI prevalence in 9 patients who did not receive premedication was 33% (3/9), which was not significantly different from patients who received premedication at 46% (56/121). Prevalence in patients on concomitant use of immunomodulator was 23% (7/31), which was significantly lower than 53% (52/99) in the patients that were not receiving an immunomodulator at the time ( P = 0.003). Infliximab therapy duration was significantly longer in ATI positive patients comparing with negative patients (26.8 ± 23.9 months versus 16.9 ± 19.2 months; respectively). None of other lab results and demographic parameters (age, gender, BMI) was associated with positive ATI. We investigated potential factors that may affect infliximab levels including age, gender, BMI, CRP, fecal calprotectin, duration of treatment, premedication and ATI presence. A statistically significant correlation was only found for detectable infliximab levels with higher BMI and with negative ATI ( P < 0.05). Interestingly, detectable infliximab levels were noted more in premedication group compared to no premedication (98% versus 89%), however the association did not reach statistical significance ( P = 0.06). No significant associations were found in all other variables. Conclusions: Our data suggests that premedication does not appear to decrease the prevalence of ATI formation. As has been suggested by prior studies, our study confirmed that use of dual therapy with addition of immunomodulator does lead to less ATI formation. Interestingly, premedication was more likely to be associated with a detectable infliximab level.